(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Nomophobia and smartphone addiction are behavioural disorders that are maladaptive and affect 21st-century digital natives anywhere, everywhere. This study investigated Effect of Nomophobia on the Educational Development in the Niger Delta within the framework of quantitative methodology of non-experimental correlational research design. The participants consisted of 300 students Ignatius Ajuru University of Education, Rivers State, Nigeria. Four research questions were answered in the study using the statistical tools of frequency, percentage, mean, standard deviation, Pearson product- moment correlation coefficient, and multiple regression analysis. Results showed that majority of the pre-service mathematics suffered from nomophobia and smartphone addiction. There was a positive relationship between smartphone addiction and nomophobia and nomophobia was a significant predictor of smartphone addiction among pre-service mathematics teachers. These findings nonetheless, show the need for more research on nomophobia as a predictor of smartphone addiction among the youths. Based on these findings it was concluded that universities and parents in Nigeria should find away of reducing the prevalence of nomophobia and smartphone addiction in pre-service mathematics teachers in the country.